2013
DOI: 10.1177/0956797612457782
|View full text |Cite
|
Sign up to set email alerts
|

Attention Restores Discrete Items to Visual Short-Term Memory

Abstract: When a memory is forgotten, is it lost forever? Our study shows that selective attention can restore forgotten items to visual short-term memory (VSTM). In our two experiments, all stimuli presented in a memory array were designed to be equally task relevant during encoding. During the retention interval, however, participants were sometimes given a cue predicting which of the memory items would be probed at the end of the delay. This shift in task relevance improved recall for that item. We found that this ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
124
5
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 21 publications
18
124
5
9
Order By: Relevance
“…Whereas spatial retro-cues are known to strongly affect the content of visual memory (Astle et al, 2012;Griffin & Nobre, 2003;Landman et al, 2003;Makovski, Sussman, & Jiang, 2008;Murray, Nobre, Clark, Cravo, & Stokes, 2013;Rerko & Oberauer, 2013;Rerko, Souza, & Oberauer, 2014;Sligte et al, 2008), few studies have addressed the role of FBA during VSTM maintenance. In these studies, colored retrocues identified one of several colored objects held in memory and participants reproduced their orientation (Heuer & Schubö, 2016;Li & Saiki, 2015;Pertzov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas spatial retro-cues are known to strongly affect the content of visual memory (Astle et al, 2012;Griffin & Nobre, 2003;Landman et al, 2003;Makovski, Sussman, & Jiang, 2008;Murray, Nobre, Clark, Cravo, & Stokes, 2013;Rerko & Oberauer, 2013;Rerko, Souza, & Oberauer, 2014;Sligte et al, 2008), few studies have addressed the role of FBA during VSTM maintenance. In these studies, colored retrocues identified one of several colored objects held in memory and participants reproduced their orientation (Heuer & Schubö, 2016;Li & Saiki, 2015;Pertzov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A valid retro-cue could stop this diffusion, or reduce interference with distractor orientations (Pertzov et al, 2013). Alternatively, the entire representation may fade out (Wei et al, 2012), be suddenly lost (Zhang & Luck, 2009), or no longer available for recall, unless selected by retrospective attention (Murray et al, 2013). A proper evaluation of these scenarios calls for a manipulation of set-size or incentives to trade off quality and quantity of memory representations (Fougnie, Cormiea, Kanabar, & Alvarez, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Participants have to judge in which direction (e.g., left or right) the probe stimulus has changed. The degree of displacement is varied, allowing researchers to measure precision as the slope of the psychometric function relating change identification accuracy to the size of a change, and the probability of reporting information from memory (as opposed to guessing) as the asymptote of the psychometric function at large sizes of change (Bays & Husain, 2008;Murray, Nobre, Clark, Cravo, & Stokes, 2013).…”
Section: Measuring the Benefits And Costs Of Retro-cuesmentioning
confidence: 99%
“…So far, all studies assessing retro-cue effects in continuous tasks have consistently reported benefits in the probability of retrieving the retro-cued item (Gunseli, van Moorselaar, Meeter, & Olivers, 2015;Makovski & Pertzov, 2015;Murray et al, 2013; Souza, manuscript submitted for publication; Souza, Rerko, Lin, & Oberauer, 2014;Souza, Rerko, & Oberauer, 2016;van Moorselaar, Gunseli, Theeuwes, & Olivers, 2015;Wallis, Stokes, Cousijn, Woolrich, & Nobre, 2015;Williams, Hong, Kang, Carlisle, & Woodman, 2013). Regarding the precision of recall as measured by the mixture model, the findings are mixed.…”
Section: Measuring the Benefits And Costs Of Retro-cuesmentioning
confidence: 99%
See 1 more Smart Citation